Lactobacillus plantarum MH-301 as an effective adjuvant to isotretinoin in the treatment of acne vulgaris: a randomized and open-label trail - Liang, Lili; Qi, Xinyue; Jiang, Xiaoke; Chen, Tingtao; Dong, Lina (Frontiers in Medicine, 2024)
Introduction: Acne vulgaris is a common chronic inflammatory skin disease originating in the sebaceous gland units of the skin follicles. Isotretinoin is presently the primary choice for the treatment of acne vulgaris. However, it could induce several adverse reactions like diarrhea, cheilitis, headache, elevated triglyceride levels and risk of inflammatory bowel disease and depression. Hence, it is imperative to seek an alternative therapy.Methods: 105 patients were randomly divided into 3 groups, and received a baseline treatment of oral doxycycline for the initial 4 weeks. Group I received isotretinoin oral for 12 weeks; Group P received oral L. plantarum MH-301 treatment for 12 weeks; Group IP received combined treatment with oral probiotics and oral isotretinoin for 12 weeks. The number of skin lesions was recorded at 0, 4, 8, and 12 weeks during the treatment to compare the efficacy of each intervention, and skin and fecal samples were collected from patients at 12 weeks for high-throughput sequencing to explore the microbiota differences between various groups.Our results revealed that the combination of L. plantarum MH-301 with isotretinoin significantly reduced the number of skin lesions in patients compared to using L. plantarum MH-301 and isotretinoin alone (p < 0.001). Additionally, skin microbiome High-throughput analysis indicated the restorative effects of L. plantarum MH-301 on skin microbial diversity while also observing a reduction in the main microbiota of skin lesions, Propionibacterium and Corynebacterium.Meanwhile, gut microbiome High-throughput analysis showed that it could regulate disorders of the intestinal microbiota and increased the abundance of probiotics such as Lactobacillus, Bifidobacterium, Coprococcus and Bacteroides genera.In conclusion, L. plantarum MH-301 could be used in combination with isotretinoin for optimal results in the treatment of acne vulgaris. The research conducted provides theoretical and data support for the adjuvant effect of Lactobacillus plantarum in the treatment of acne vulgaris.